An Analysis of Illocutionary Meaning of the Ritual Speech “Saeba Bunuk Hau No” in Spaha Village, Kolbano Subdistrict, South Central Timor Regency - Lette, Ofi Yunarti; Isu, Rudolof Jibrael; Radja, Markus D. (Talenta Publisher, 2025)
The title of this research is an analysis of illocutionary meaning of Saeba bunuk hau no in Spaha village, Kolbano subdistric, South Central Timor Regency with the problems are 1. What are the types of Illocutionary meaning in the ritual speech entitled“Saeba Bunuk Hau No” 2. What types of Illocutionary ritual speech are mostly used in the ritualspeech entitled “Saeba bunuk hau no”. The aims of this research are 1. To know the types of Illocutionary used in the ritual speech entitled “Saeba bunuk hau no” 2. To know the types of Illocutionary ritual speech are mostly used in theritual speech entitled “Saeba bunuk hau no”. The theory that the writer used is the theory of speech act, which this theory inspects how we can find out the illocutionary meaning. The method that the writer used is descriptive qualitative method with techniques of collecting the data are reading the previous research result, find the utterances, analyze the meaning of utterances to identify the types of illocutionary and to know the types of illocutionary are mostly used in the ritual speech Saeba bunuk hau no in the Spaha Village, Kolbano Subdistric, South Central Timor Regency. From the results of this study the writer found that there were five types of illocutionary meaning of Saeba bunuk hau no, namely: Assertive, Directive, Expressive, Comisive and Declarative and the most widely used type of illocutionary was Assertive, Directive and Declarative because this types of illocutionary was used to convey a specific purpose.